Metoda Penyiapan Konjugat (DOTA)n-[Dendrimer PAMAM]-(Trastuzumab)m Sebagai Bahan Radiofarmaka Radioimunoterapi (177Lu-DOTA)n-[Dendrimer PAMAM]- (Trastuzumab)m - RIEN RITAWIDYA; SRI SETYOWATI; CECEP TAUFIK RUSTENDI; MASKUR MASKUR; MARTALENA RAMLI; BASUKI HIDAYAT; MUHAMMAD SUBUR; ABDUL MUTALIB; JOHAN MASHYUR (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Radioimmunotherapy is one of modalities means of treatment for cancer that exploits the antibody monoclonal specificity to bind to its receptor and the ability of alfa or beta radiation in destroying cancer cells. Trastuzumab is humanized IgG1 monoclonal antibodies which selectively bind to extracellular domain of Human Epidermal Growth Factor Receptor-2 (HER-2). HER-2 has now became a target receptor for treatment of human breast cancer due to their overexpression in the human breast cancer cell surface. This study was aimed in developing a method for preparation of (DOTA) n-[Dendrimer PAMAM]-(trastuzumabm conjugate, a precursor of (177Lu-DOTA)n-PAMAM-(trastuzumab) m radioimmunoconjugate, which is expected to be potential for breast cancer radioimmunotherapy. The conjugate was prepared through several conjugation steps. Characterization of (DOTA)n-[Dendrimer PAMAM]-(trastuzumab)m which was carried out by using a HPLC equipped size exclusion column (SEC) gave a clean peak with retention time (tR) of 10.53 mins which was slower compared to tR of its precursor unconjugated trastuzumab (10.70 mins). This result indicated that molecular weight of (DOTA)n-[Dendrimer PAMAM]-(trastuzumab)m was bigger than its precursor (unconjugated trastuzumab) and pure. The purity of (DOTA)n-[Dendrimer PAMAM]- (trastuzumab)m was verified by measuring the Rf of 177Lu-radiolabeled-(DOTA)n-[Dendrimer PAMAM]-(trastuzumab)m using instance thin layer chromatography-silica gel (ITLC-SG). The ITLC-SG of (DOTA)n-[Dendrimer PAMAM]-(trastuzumab)m which was radiolabeled with 177Lu- gave a clean peak with Rf of <0.3, while the precursors which were regards as impurities, (free 177Lu in form 177Lu-EDTA, 177Lu-DOTA, and 177Lu- dendrimer PAMAM which was incubated as non specific binding), all of them gave Rf of >0.6. These ITLC results indicated that (DOTA)n-[Dendrimer PAMAM]-(trastuzumab)m radiolabeled with 177Lu was pure.